Translation as Rewriting: Cultural Theoretical Appraisal of Shakespeare’s "Macbeth" in the Ewe language of West Africa - Agbozo, G. Edzordzi (Multicultural Shakespeare: Translation, Appropriation and Performance, 2018)
The cultural turn in translation theory brought attention to the idea that translation is not a purely linguistic phenomenon but one that is also constrained by culture. The cultural turn considers translation as a rewriting of an original text. In this paper, I attempt to find reflections of the cultural turn in a translation into an African language. As such, the paper reads William Shakespeare’s Macbeth in the Ewe language of West Africa, Shakespeare ʄe Makbet, as rewriting. Walter Blege is the translator and the Bureau of Ghana Languages is the publisher of the target text meant for Ewe language audience in Ghana. The target text is for learning and acquiring the Ewe language especially in the area of developing reading comprehension skills. Following Andre Lefevere and Jeremy Munday, this paper suggests that Shakespeare ʄe Makbet is a rewritten text as it follows some cultural constraints in its translation. The study provides insight into the motivations for some of the translator/rewriter’s choices. Given the less attention paid to the Ewe language and many other African languages, the paper proposes translation as a socio-psychological tool for revitalizing interest in the learning and acquisition of African and other lesser-known languages.